Uncovering the antecedents of trust in social commerce: an application of the non-linear artificial neural network approach. Issue 3 (31st January 2022) - Alnoor, Alhamzah; Al-Abrrow, Hadi; Al Halbusi, Hussam; Khaw, Khai Wah; Chew, XinYing; Al-Maatoq, Marwa; Alharbi, Raed Khamis
Abstract : Purpose: The internet creates ample opportunities to start a mobile social commerce business. The literature confirms the issue of customer trust for social commerce businesses is a challenge that must be addressed. Hence, this study aims to examine the antecedents of trust in mobile social commerce by applying linear and non-linear relationships based on partial least squares structural equation modeling and artificial neural network model. Design/methodology/approach: This study applied a non-linear artificial neural network approach to provide a further understanding of the determinants of trust in mobile social commerce based on a non-linear and non-compensatory model. Besides, a questionnaire was distributed to 340 social commerce customers in Malaysia. Findings: The conceptual framework for investigating trust in mobile social commerce has various advantages and contributions to predicting consumer behavior. The results of the study showed there is a positive and significant relationship between social support, presence and unified theory of acceptance and use of technology2 (UTAUT2). In addition, UTAUT2 has fully mediated the relationship between social support, presence and trust in social commerce. Finally, the results concluded the relationship between UTAUT2 and trust in social commerce would be stronger when the diffusion of innovation and innovation resistance is high and low, respectively. Research limitations/implications: The current study provides a novel perspective on how customers can trust social m-commerce to provide real solutions to managers of encouraging e-marketing among consumers. Practical implications: This paper shows how businesses can develop trust in social m-commerce in Malaysian markets. The findings of this study probably could be extended to other businesses in Asia or other countries. Because trust in social e-commerce has a dynamic role in consumer behavior and intention to purchase. Originality/value: This study provided a new perspective on mobile social commerce and paid more attention to an investigation of such emerging commerce. The originality of this study is embodied by investigating an integrated model that included different theories that presented new directions of trust in mobile social commerce through social and behavioral determinants.